Diffusion of Brazil’s food policies in international organisations: assessing the processes of knowledge framing - Carolina Milhorance (Policy & Society, 2020)
This article focuses on the political dynamics shaping policy agendas and prescriptions in international organisations (IOs). It elucidates the interactions of Brazil’s state and non-state actors with international bureaucrats, and their role in framing the strategy and recommendations promoted by the UN Food and Agriculture Organization and Portuguese-speaking Community of Countries regarding the challenge of tackling food insecurity. The research builds on semi-structured interviews and a significant number of institutional documents, and combines constructivist international relations theory and sociological approaches to policy transfer/diffusion to explore the circulatory processes of policymaking. Aside from enhancing understanding of the micro-dynamics of framing and diffusion of policy ideas and prescriptions in IOs, the article provides information on the dissemination of policy solutions from the global south towards IOs and subsequently, to other developing countries.